Islam as Science and Doctrine in Preventing the Emergence of Radicalism in Generation Z - Eri Murniasih; Utang Ranuwijaya; Muhajir M; Ummu Habibah (al-Afkar, Journal For Islamic Studies, 2024)
Islam as a religion has two sides which can be understood as knowledge whose truth can be tested and on the other hand as a doctrine that must be believed and implemented with faith. These two sides have the potential to prevent the growth of radicalism which is often associated with an “offside” understanding of religion. The aim of this research is to explore the role of Islam as a science and doctrine in preventing the emergence of radicalism in Generation Z, especially among students at Serang Raya University. In the era of digital and rapidly developing globalization and the very massive dissemination of information, Generation Z, with its characteristics as a digital native, is vulnerable to exposure to a variety of diverse information, including content that contains radical ideology so that it can disrupt concentration to understand Islam more deeply. An approach based on a moderate and comprehensive understanding of the Islamic religion is crucial in facing this challenge. Through literature studies and qualitative research methods, this article analyzes how Islamic religious education based on the values of rahmatan lil'alamin and moderation can be an effective bulwark in fending off radicalism. This article concludes that the integration of comprehensive religious education and the use of appropriate information technology can prevent the spread of radical ideology among Generation Z.